The Role of Gender on Biosecurity Practices in Beef Cattle Supply Chain Farms in Bone Regency, South Sulawesi - Lestari, Veronica Sri; Rahardja, Djoni Prawira; Sirajuddin, SittiNurani (ExcelingTech, 2020)
Abstract. The aim of this study was to know the role of gender on biosecurity practices in beef cattle farms in Bone Regency, South Sulawesi. Total sample was 51 beef cattle farmers which was chosen through purposive sampling. Data were collected through observation and depth interview by using questionnaire. There was 22 questions which were divided into 5 sub variables: participation, isolation, sanitation, traffic control and other activities. Guttman scale was used to know whether beef cattle farmers take a part on those activities or not. The score was 1 if they DO, and the score was 0 if they DO NOT DO. Data were calculated by using SPSS version 23.0 and were analyzed descriptively by using percentage table. The results showed that the highest percentage was sanitation (69.02%), and the lowest percentage of the role of gender on biosecurity practices in beef cattle farms was participation (13.07%) which consisted of training, seminar and looking for information. On average, the role of men were greater than the role of women on biosecurity practices in beef cattle farms in Bone Regency, South Sulawesi: 54.70% and 45.30% respectively.